Features Of Orthopedic Treatment For Complete Adentia (Eurasian Medical Research Periodical, 2024)
Many people do not even imagine what this dental disease is. But those who are faced with this experience what happened as a serious problem that significantly reduces the quality of life. Adentia – this term means the absence of teeth. Complete adentia means that a person has no teeth at all. There is not a single tooth in either the upper or lower row. Nowadays, traditional prostheses have not lost their popularity, although they are not a high-quality treatment for adentia. There are several types of such prostheses